ChemInform Abstract: Iridium‐Catalyzed Enantioselective Allyl—Alkene Coupling. Issue 35 (2nd September 2014) - Hamilton, James Y.; Sarlah, David; Carreira, Erick M.
Abstract The products are contaminated with minor amounts (<20:1 in most cases) of double bond isomers like (VI).